Program Bantu Diri Terapi Kognitif Perilaku: Harapan bagi Penderita Depresi - Susana, Tjipto; Parmadi, Eko Hari; Adi, Puspaningtyas Sanjoyo (Faculty of Psychology, Universitas Gadjah Mada, 2015)
This article is the first-phased report of a research through a testing of cognitive behavioral therapy module. The subjects involved in this research were 27 students who were experiencing mild to moderate depression. The research design was experiment with a pretest and posttest group. Instruments used in this study were Back Depression Inventory-II (BDI-II), Automatic Thought Questionnaire (ATQ), Dysfunctional Attitude Scale (DAS). The data was analized using paired t-test. Based on qualitative analysis, the results showed that in general it was easy for the students to understand and do the module independently. This module was very helpful for them in managing thoughts and feelings and specifically in the automatic negative thoughts, dysfunctional thinking, and rules. Nevertheless, this module did not cover the core belief. The results of the t test (t (25)=9.2; p